The muscle pre-activity timing of the hamstrings and quadriceps during 180° and 360° rotational jump landings in healthy female subjects - Daisuke Bai; Yohei Okada; Takahiko Fukumoto; Munehiro Ogawa; Yasuhito Tanaka (Elsevier, 2019)
Background/Objective: The muscle activity before the initial contact between during jump landings is referred to as the pre-activity. The muscle pre-activity that occur during jump landing are considered to be an important predictor of non-contact anterior cruciate ligament (ACL) injury risk. ACL injury prevention programs have been widely conducted; these programs are generally focused on increasing the muscle pre-activity and include rotational jump landing. The purpose of this study was to investigate the timing of the muscle pre-activity of the hamstrings and quadriceps during 180° and 360° rotational jump landing. Methods: The participants were 10 healthy females. Electromyography was conducted on the knee joint muscles of the left leg (the non-dominant leg) during clockwise 180° and 360° rotational jump landings. Results: The muscle pre-activities during 180° rotational jump landing was VM: 35.68 ± 11.22 msec, RF: 38.05 ± 14.77 msec, VL: 47.10 ± 19.96 msec, BF: 115.63 ± 30.48 msec and SM: 136.45 ± 47.52 msec. And the muscle pre-activities during 360° rotational jump landing was VM: 45.25 ± 17.41 msec, RF: 42.38 ± 13.35 msec, VL: 48.75 ± 19.20 msec, BF: 132.20 ± 46.74 msec and SM: 140.70 ± 40.64 msec. For both the 180° rotational jump landing and the 360° jump landing, the pre-activities of the hamstrings occurred significantly earlier than those of the quadriceps (p < 0.01). Conclusion: The results of the present study indicate that it may be beneficial for ACL injury prevention programs to include rotational jump landing tasks. Keywords: Rotational jump landing, Muscle pre-activity timing, Electromyography, Knee joint, ACL injury prevention